Intervensi Non-Farmakologis untuk Bradikardia Simptomatik: Studi Mobilisasi Progresif dan Manajemen Energi di Ruang High Care Unit - Jurana, Jurana; Lilianty Syattar, Elly (Yayasan Mandar Indonesia, 2025)
Symptomatic bradycardia is a condition of slowed heart rate accompanied by symptoms such as dizziness, fatigue, and activity intolerance. Non-pharmacological interventions such as progressive mobilization and energy management are believed to improve patient hemodynamics. This study aimed to analyze the effects of progressive mobilization and energy management on hemodynamic parameters in a patient with symptomatic bradycardia. A descriptive case study was conducted on a 71-year-old male patient with symptomatic bradycardia, hypertension, and other comorbidities treated in the High Care Unit (HCU) of Dr. Wahidin Sudirohusodo Hospital. Interventions were carried out over three days, including passive exercises, active exercises, sitting, and structured energy-based activity management. Parameters of blood pressure, heart rate, respiratory rate, and oxygen saturation were recorded before and after the intervention. Results showed an increase in Barthel Index score from 2 to 8, stabilization of blood pressure and heart rhythm, and improved respiration. Progressive mobilization and energy management are effective in stabilizing hemodynamics and enhancing activity tolerance in symptomatic bradycardia patients.